Case report: Blood purification effectively relieves multiple system failure in patient with rabies - Kuang, Daibin; Luo, Ming; Chen, Jiabao; Liang, Congmin; Cai, Ziwei; Yuan, Zeqiang; Zhou, Zhuandi; Chen, Jialong; Fu, Chunlai (Frontiers in Public Health, 2022)
Rabies is an infectious disease of animal origin with a high mortality rate. In the early stages of rabies, the rabies virus is usually undetectable in saliva and cerebrospinal fluid. And there are still no effective drugs and treatments. Here, we present a case in which blood purification alleviated multi-system failures. The patient was a 45-year-old woman who presented with the fear of water and wind, restlessness and hyperactivity. Rabies virus was detected in her saliva by high-throughput sequencing (NGS) and Polymerase Chain Reaction (PCR). Based on typical clinical symptoms and the result of NGS and PCR, the patient was diagnosed as a confirmed case of rabies. Hemodialysis combined with antiviral therapy and intensive care unit treatment (ICU) can effectively relieve circulatory failure, respiratory failure and renal failure. Finally died of brain death on the 34th day of admission. The case report showed that blood purification was positive for rabies-induced organ failure. Blood purification combined with antiviral therapy can prolong the lives of rabies patients to some extent.